Fusion of a family 20 carbohydrate‐binding module (CBM20) with cyclodextrin glycosyltransferase of Geobacillus sp. CHB1 improves catalytic efficiency. (19th April 2017) - Jia, Xianbo; Guo, Yonghua; Lin, Xinjian; You, Minsheng; Lin, Chenqiang; Chen, Longjun; Chen, Jichen
Abstract : Cyclodextrin glycosyltransferase (CGTase) is an important industrial enzyme for production of cyclodextrins (CDs) from starch by intramolecular transglycosylation. CGTase consists of five domains labeled A to E. For optimizing catalytic activity of CGTase, CGTase of Geobacillus sp. was fused with the family 20 carbohydrate‐binding module (CBM) of the Bacillus circulans strain 251 CGTase. The CBMbc251 that has a low binding free energy with maltohexaose, was selected by in silico design. Then the fusion enzyme, CGTΔE‐CBMbc251, was constructed by fusing the CBMbc251 to the C‐terminal region of CGTΔE. The fusion enzyme displayed an even greater enhancement of total α‐cyclization activity (40.2%) and γ‐cyclization activity (181.58%). Optimal reaction pH range was wilder and the thermal stability was better under 50 and 60 °C. Compared to the wild‐type CGTase, the fusion enzyme showed a remarkable decrease in Km and a slight alteration in Vmax. The enhancement of soluble starch catalytic efficiency might be due to the changes of substrate binding ability in the critical substrate binding sites between the CBM and starch granule.